Towards an improved understanding of local uterine innate immunity and histological change in postpartum cows : relevance to fertility? - Chapwanya, Aspinas (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2009)
Uterine involution in postpartum (pp) cows is necessary for establishment of the next pregnancy. Endometritis perturbs involution, impairs uterine function and causes systemic illness leading to significant involuntary cow culling. This costs dairy farmers and national exchequers €2.5 billion annually world-wide. At calving, bacteria enter the uterus via the open cervix presumably stimulating a cascade of innate immune defence events that culminate in transient uterine inflammation. In most cows this is followed by the clearance of infection, resolution of inflammation and resumption of cyclic activity.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.